Past and Present Permafrost Temperatures in the Abisko Area: Redrilling of Boreholes - Margareta Johansson; Jonas Åkerman; Frida Keuper; Torben R. Christensen; Hugues Lantuit; Terry V. Callaghan (AMBIO, 2011)
Monitoring of permafrost has been ongoing since 1978 in the Abisko area, northernmost Sweden, when measurements of active layer thickness started. In 1980, boreholes were drilled in three mires in the area to record permafrost temperatures. Recordings were made twice per year, and the last data were obtained in 2002. During the International Polar Year (2007–2008), new boreholes were drilled within the ‘Back to the Future’ (BTF) and ‘Thermal State of Permafrost’ (TSP) projects that enabled year-round temperature monitoring. Mean annual ground temperatures (MAGT) in the mires are close to 0°C, ranging from -0.16 to -0.47°C at 5 m depth. Data from the boreholes show increasing ground temperatures in the upper and lower part by 0.4 to 1°C between 1980 and 2002. At one mire, permafrost thickness has decreased from 15 m in 1980 to ca. 9 m in 2009, with an accelerating thawing trend during the last decade.